Overview of Risky Sexual Behaviour Among Teenagers in Bajera Village, Selemadeg District, Tabanan Regency, Bali, 2022 - Ni Wayan Widarini; Ni Wayan Ariyani; Ni Ketut Somoyani (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2023)
Teenagers' dating style at this time tends to be risky, for example by kissing, touching sensitive parts, until some have had a relationship like husband and wife. This incident is inseparable from the sociodemographic characteristics of the adolescents themselves which include age, gender, education level, family roles, peers roles, and exposure to pornographic media. The purpose of this study was to determine the description of risky sexual behavior in adolescents in Bajera Village, Selemadeg District, Tabanan Regency Bali in 2022. This study was a descriptive study with cluster random sampling as a sample in Banjar Dinas Bajera Jero. The research sample was 99 people using google form. Adolescent characteristics were assessed by univariate technique including risky sexual behavior. Data processing is done with a computerized system. The results showed that the risky sexual behavior of adolescents in Bajera Village was in the less category as many as 86 (86.87%) respondents. For the sociodemographic characteristics of adolescents in the form of the highest age at the end of 63 (63.64%), the highest gender was in women 57 (57.58%), the highest education level was in SMA / equivalent 45 (45.46%), the highest family role was in good category 49 (49.50%), the highest peer role in the less category 79 (79.80%), and internet media as the pornographic media of choice the most.